Politics: A limit to the competence of Judicial Power. A purpose of the judgment of the Supreme Court Marelic with SERVEL and other, of november 8, 2017 - Silva Irarrázaval, Luis Alejandro; Díaz, Gustavo Adolfo (Derecho Público Iberoamericano, 2020)
The case of Marelic con Servel y otros is quite unique within the caselaw of the Chilean Supreme Court, because it declares a certain matter (i.e. the right to vote of inmates) as beyond the purview of judicial power. Correspondingly, it hands the solution on the political branches. The purpose of this commentary is to develop the premises on which the case rests, and to envisage its scope. Particularly, we intend to underscore how there are problems which are political in nature, and consequently they should be handle by the political branches, namely Congress and the Executive Power, not the Judiciary.